Mondor’s Disease: A Rare Condition Revisited – Insights from Literature - Skorulska, Iwona; Grzeszczuk, Paulina; Głowacka, Aleksandra; Kozakiewicz, Julia; Okońska, Aleksandra; Kościelecki, Kamil; Długozima, Patrycja; Mączewska, Klaudia; Grywińska, Weronika Barbara; Kalisz, Agnieszka (Quality in Sport, 2025)
Introduction: This review paper aims to systematize the current knowledge about Mondor's disease, its etiology and epidemiology, diagnostic methods, differential diagnosis, and therapeutic approaches. Furthermore, it examines the prognosis and potential complications based on a comprehensive review of the available literature. Materials and methods: A review of selected literature in the PubMed database was conducted, using the following keywords: ,,Mondor’s disease”, ,,vein thrombosis”, ,,superficial thrombophlebitis”. Summary: Mondor’s disease is a rare, self-limiting superficial thrombophlebitis, primarily affecting the anterior chest wall but also documented in the abdomen, axilla, groin, and penis. Its etiology remains unclear, though mechanical stress, inflammation, and hypercoagulability are implicated. It predominantly affects middle-aged women. Though benign, its clinical presentation may mimic malignancies, causing significant distress. Diagnosis is primarily clinical, based on a palpable, tender, cord-like structure without systemic symptoms. Imaging, particularly ultrasonography, is warranted when malignancy is suspected. Mammography or Magnetic Resonance Imaging may be used to exclude neoplastic conditions. Management is conservative, focusing on NSAIDs, topical therapies, and activity modification. Anticoagulation is generally unnecessary but may be considered in extensive thrombosis. Surgical intervention is rare. Prognosis is favorable, with spontaneous resolution within weeks, though secondary cases require treatment of the underlying condition. Conclusions: Healthcare providers must recognize Mondor’s disease to ensure accurate diagnosis and effective management. While conservative treatment remains the standard, further research into its pathophysiology may refine diagnostic and therapeutic strategies. In recurrent or secondary cases, vigilance for thrombotic disorders or malignancies is essential for comprehensive patient care.